2018
DOI: 10.1007/s10569-018-9854-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term attitude dynamics of space debris in Sun-synchronous orbits: Cassini cycles and chaotic stabilization

Abstract: Comprehensive analysis of space debris rotational dynamics is vital for active debris removal missions that require physical capture or de-tumbling of a target. We study the attitude motion of used rocket bodies acknowledgedly belonging to one of the categories of large space debris objects that pose an immediate danger to space operations in low Earth orbits. Particularly, we focus on Sun-synchronous orbits (SSO) with altitudes in the interval 600 ÷ 800 km, where the density of space debris is maximal. Our ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They applied the material point method to describe the impact process of a debris object and spacecraft. Efimov et al [16] investigated the attitude evolution of space debris in SSO combining perturbation methods and a numerical approach. It was shown that the orbital precession and influence of orbital motion on induced eddy currents might make a significant impact on the attitude evolution.…”
Section: Introductionmentioning
confidence: 99%
“…They applied the material point method to describe the impact process of a debris object and spacecraft. Efimov et al [16] investigated the attitude evolution of space debris in SSO combining perturbation methods and a numerical approach. It was shown that the orbital precession and influence of orbital motion on induced eddy currents might make a significant impact on the attitude evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Rawashdeh [26] studied the attitude analysis of small satellites using model-based simulation. Efimov et al [27] discussed about long-term attitude dynamics of space debris for sun-synchronous orbits and studied about Cassini cycles and chaotic stabilization. Chang [28] gave an idea of stability, chaos detection, and quenching chaos for the swing equation system.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2012 study, Yanagisawa and Kurosaki used photometric light flashes to determine that the object possesses a rotational period of 41.00 seconds, corresponding to an angular rate of = 0.153 / about the major axis [12]. The effects of eddy current damping, as described by Efimov et al [13], Praly et al [14], and Williams and Meadows [15], are likely to have considerably reduced the spin rate of the object during the eight years since the photometric observations took place. However, since no future studies have taken place on the same object, this study makes the assumption that the spin rate is still unchanged.…”
Section: Introductionmentioning
confidence: 99%